2012
DOI: 10.1177/1356336x12457293
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the spaces of reflection

Abstract: Innovation in enhancing the reflective abilities of physical education trainee teachers was explored in this study through establishing peer ‘training buddies’ during their school placements. Opportunities for active engagement in peer- and self-reflection were provided to full-time Post-Graduate Secondary Physical Education trainee teachers ( n = 23). Data were collected through surveys, focus group interviews and trainee reflections shared through online discussion boards. Prior to their first school placeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…At the same time, novice teachers in Forbes' (2004) study suggested that their lack of teaching experience did not influence their peer mentoring. Similar findings concerning prior knowledge and experience were also revealed for student teachers (Lamb, Lane, & Aldous, 2013;Ritchie & Peters, 2001;Schuck, 2003).…”
Section: Contexts Influencing Ptl Activitiessupporting
confidence: 74%
See 2 more Smart Citations
“…At the same time, novice teachers in Forbes' (2004) study suggested that their lack of teaching experience did not influence their peer mentoring. Similar findings concerning prior knowledge and experience were also revealed for student teachers (Lamb, Lane, & Aldous, 2013;Ritchie & Peters, 2001;Schuck, 2003).…”
Section: Contexts Influencing Ptl Activitiessupporting
confidence: 74%
“…Hypothesis 9: PTL activities become more effective when interpersonal factors, such as trust and respect, are taken into account The findings showed that interpersonal factors influenced the success of PTL activities. Trust appeared essential for any activity (Biasutti, 2011;Estebaranz et al, 1999;Eteläpelto et al, 2005;Fransen et al, 2011;Helleve, 2007;Hew & Hara, 2007;Lamb et al, 2013;Shin et al, 2007;Wilkins et al, 2009). As Fransen et al demonstrated: " … mutual trust appears to be conditional" (2011, p. 1109).…”
Section: Contexts Influencing Ptl Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The buddy chosen was usually someone they had interacted with as part of the community organisation volunteer programme. This buddy system was used as a means of support for the peer educator to learn and receive feedback as the presenter practised delivering the presentation (Lamb, Lane, and Aldous 2013). A selfreflection report (Bennett, Rolheiser, and Stevahn 1991) and a fidelity checklist (online supplementary material A.2) (Bellg et al 2004) provided further opportunity to facilitate self-directed learning and to ensure programme fidelity respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, participation strategies such as self-assessment, dialogue qualification, or coassessment are possible in this evaluative model. In the case of PE, different studies have demonstrated the benefits of involving students by using self-assessment situations as well as peer assessment or coassessment [11][12][13][14][15]. Reviews of different works on assessment practices over a range of contexts and points in time in PE reveal that despite the prevalence of the formative assessment paradigm, grading models continue to predominate in PE teachers' evaluative practices, with low student participation [16][17][18].…”
Section: Self-assessment As a Formative And Shared Assessment Process In Physical Educationmentioning
confidence: 99%